Elastisitas Modal dan Tenaga Kerja Terhadap Tingkat Produksi pada Industri Kecil (Studi Kasus pada Industri Batik Banyumas) - Lilis Siti Badriah; Nunik Kadarwati; Neni Widayaningsih (EKO-REGIONAL, 2008)
The purpose of this research is to analyze production elasticity to capital and labor at Batik Banyumas industry. The object of this research is Batik Banyumas business using cross-section data on 2008. The data are capital, especially investment capital, and labor as direct input, and also the quantitiy of Batik production. Primary data is obtained by interview to responden and secondary data is collected from Industry, Trade, and Cooperation Department. The method analysis is multiple regression with Constant Elasticity Substitution (CES) of production function model.  The results of research indicate that:1.   Investment capital and labor influence significantly to the quantity of Batik Banyumas production, partially and simultaneously.2.   Totally,  investment capital,  labor,  and substitution process of labor to capital investment to the quantity of batik production are elastic. Partially, investment capital is elastic but labor and substitution process of labor to capital investment are inelastic.3.    Input substitution rate (between investment capital and labor) with r value indicator is 0,748044991 (<1).  It means that substitution process between investment capital and labor is inelastic and it’s difficult to do. Keywords: direct input, capital investment, labor, partial and total elasticity,  constant elasticity substitution